2018
DOI: 10.1016/j.ijbiomac.2018.02.113
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of food-grade nanofibres from whey protein

Abstract: In this study, electrospinning has been employed to produce micro to nano scale fibres of whey protein in order to investigate their potential for use in the food industry. Initially, spinning of pure whey protein proved challenging; so in order to facilitate the spinning of freshly prepared aqueous solutions, small amounts of polyethylene oxide (as low as 1% w/w in solution) were incorporated in the spinning solutions. The electrospun composite polyethylene-oxide/whey fibres exhibited diameters in the region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…It was shown that while performing electrospinning with the solutions containing 40 kDa dextran, fibers couldn't be obtained for any mixing ratio. In another recent study by [227] whey protein/PEO composite nanofibers were fabricated by adding much less (1 wt. %) of PEO in whey protein.…”
Section: Whey Protein and Its Isolatesmentioning
confidence: 99%
“…It was shown that while performing electrospinning with the solutions containing 40 kDa dextran, fibers couldn't be obtained for any mixing ratio. In another recent study by [227] whey protein/PEO composite nanofibers were fabricated by adding much less (1 wt. %) of PEO in whey protein.…”
Section: Whey Protein and Its Isolatesmentioning
confidence: 99%
“…A single and fast whipping viscoelastic jet was produced from the tip of the Taylor cone and then split into many small jets. The small jets were further stretched in the electrostatic field, ultimately resulting in nanofiber products [36]. The PVP was then removed by calcination to form mesoporous hollow SnO 2 nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the electrospinning technique is currently being studied as an emerging advancement for the production of food-grade nanofibers from WP [216]. Electrospinning has been employed to produce micro- to nano-scale fibers as a carrier system to evaluate their potential utilization in food [217]. The ability to generate nanofibers from whey proteins exhibits an opportunity to exploit their inherent benefits, along with the desirable attributes of nanofibers.…”
Section: Whey Proteins: Research Insights and Trendsmentioning
confidence: 99%